UMPSA celebrates the success of MASUM and AUG 2024 athletes - Mohd Farid, Md Ali; Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 19 June 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated the success of athletes and officials who represented the Malaysian contingent at the ASEAN University Games (AUG), along with outstanding athletes who won medals in the recent MASUM 2024 Sports Carnival.